Relationship between Leisure Time Activities and Academic Achievement: An Indian Perspective: Exploring the Impact of Leisure Time Activities on Academic Achievement (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Leisure holds a great importance in students’ timetable during their academic progress. With passage of time and evolution of technology new ways of involvement in leisure have emerged and can have both positive as well as negative impact on their academic performance. This study attempts to find the link between the time spent in leisure activities and the academic performance of students who have freshly passed class 12th examination and have been enrolled in different courses in colleges and universities. The differences in terms of gender are also examined. It is found that there is a negative relationship between leisure time activities of undergraduate students and the grades they obtain in their pre-college classes. Implications for education are also presented.